Optical microring resonator based corrosion sensing - Ahmed, R.; Rifat, A.A.; Yetisen, A.K.; Salem, M.S.; Yun, S.H.; Butt, H. (Royal Society of Chemistry, 2016)
A refractive index (RI) based corrosion sensor that could measure the oxidation of iron metal to iron-oxide was numerically investigated with a finite element method. The sensor is based on an optical microring resonator with periodically arranged iron nanodisks (NDs) in a ring waveguide (WG). The microring resonator showed a linear resonance frequency shift as iron was oxidized due to RI variation and back scattered light, as compared to conditions with no ND ring. The resonance wavelength shift depended on the number of NDs and the spacing between the NDs. Free spectral range and sensor sensitivity were 40 nm and 517 nm RIU-1 with 10 NDs with 50 nm spacing. Optimization of the sensor parameters allowed a two-fold improvement in sensitivity and achieved a quality factor of 188. The sensitivity and Q-factor showed a linear relationship with increasing ND numbers and spacing. The microring resonator based optical corrosion sensor will find applications in real-time, label-free corrosion quantification.